2004
DOI: 10.1124/dmd.104.001164
|View full text |Cite
|
Sign up to set email alerts
|

MULTIPLE NIGHT-TIME DOSES OF VALERIAN (Valeriana officinalis) HAD MINIMAL EFFECTS ON CYP3A4 ACTIVITY AND NO EFFECT ON CYP2D6 ACTIVITY IN HEALTHY VOLUNTEERS

Abstract: ABSTRACT:Valerian (Valeriana officinalis) is a popular dietary supplement. The objective of this study was to assess the influence of a valerian extract on the activity of the drug-metabolizing enzymes cytochrome P450 2D6 (CYP2D6) and 3A4. Probe drugs dextromethorphan (30 mg; CYP2D6 activity) and alprazolam (2 mg; CYP3A4 activity) were administered orally to healthy volunteers (n ‫؍‬ 12) at baseline and again after exposure to two 500-mg valerian tablets (1000 mg) nightly for 14 days. The valerian supplement c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 22 publications
4
41
1
3
Order By: Relevance
“…Valerian was traditionally thought of as a cerebral stimulant and suggested to have a 'heating property' making people feel warm, but no associated side effects were reported in clinical trials. Minimal effects on cytochrome P450 enzymes were reported in healthy subjects (Donovan et al, 2004).…”
Section: Valerian (Valeriana Officinalis)mentioning
confidence: 99%
“…Valerian was traditionally thought of as a cerebral stimulant and suggested to have a 'heating property' making people feel warm, but no associated side effects were reported in clinical trials. Minimal effects on cytochrome P450 enzymes were reported in healthy subjects (Donovan et al, 2004).…”
Section: Valerian (Valeriana Officinalis)mentioning
confidence: 99%
“…Red clover (Trifolium pretense) CYP1B1 (Roberts et al, 2004); CYP2C8 (Liang et al, 2003;Piersen et al, 2004); CYP2C9 (Lin et al, 1998;Maliakal and Wanwimolruk, 2001) (Gurley et al, 2005); CYP3A4, CYP2D6 (Donovan et al, 2004) a Clinical interactions have been noted, as reported by Tsai et al (2014). b Clinical interactions have been reported, as noted by Hu et al (2005).…”
Section: Discussionmentioning
confidence: 77%
“…However, critical assessment of these studies suggests that the clinical relevance of the findings is questionable due to various methodological limitations (Table 1). This is underlined by the available clinical interaction studies on CYP isoenzymes, which do not indicate a relevant drug interaction potential of valerian in healthy volunteers [35,37].…”
Section: Discussionmentioning
confidence: 99%
“…One of these publications [34] contains, in addition, data on animal studies. Two publications [35,37] present clinical studies on pharmacokinetic interactions. 8 studies are available on the subject of pharmacodynamic interactions, thereof two in vitro and three animal studies, one clinical study, and in addition two case reports.…”
Section: Metabolic Pathwaymentioning
confidence: 99%
See 1 more Smart Citation